METAPHOR IN COLDPLAY-FIX YOU LYRICS: COGNITIVE SEMANTICS ANALYSIS - Dewi, Shafira Anastasya (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
This research analyzes the metaphorical meanings in the lyrics of Coldplay's song